Knowledge Management sebagai Upaya Learning Organization di Sekolah Tinggi Agama Islam Yogyakarta - Muhammad Yusuf; Anisa Nur Azizah Husni (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2019)
This article aims to study knowledge management as an effort for learning organizations in STAIYO. The formulation of the problem in this study relates to the central object, the main actor, and the knowledge management process as a learning organization at STAIYO. This study used a qualitative approach with the background of knowledge management activities at STAIYO. The results of this study indicate that the central object in knowledge management in STAIYO is related to increasing member competence, which includes pedagogical competence, personal competence, professional competence, and social competence. The actors in knowledge management are certainly all structural members possessed by STAIYO. While the application process of knowledge management as an effort for learning organizations in STAIYO consists of, 1) the socialization process; regular discussions, holding seminars, including one member to attend training and/or training, 2) externalization process; documenting the results of routine discussions and making proceedings on the results of the seminar, 3) the combination process; requires every member of the organization to conduct research in each year, 4) internalization process; requires lecturers to publish in educatia (their internal journal).